Ancestral splice variation is a key substrate for rapid diversification in African cichlids - Pooja Singh; Ehsan Pashay Ahi; Anna Duenser; Marija Durdevic; Wolfgang Gessl; Sylvia Schaeffer; Julian Gallaun; Ole Seehausen; Christian Sturmbauer (Proceedings of the National Academy of Sciences, 2026)
Adaptive radiation is a major driver of biodiversity. In some of the largest radiations, increasing evidence suggests that explosive morphological diversification is often fueled by standing genetic variation and admixture, rather than de novo mutations. The rapid translation of this genetic variation into novel phenotypes through gene regulation remains poorly understood. Analyzing 200 transcriptomes from three independent but phylogenetically nested African cichlid adaptive radiations, we show that alternative splicing (AS) evolved faster than gene expression (GE), playing a pivotal role in shaping novel trophic adaptations in the youngest and most species rich radiations in Lakes Victoria and Malawi. This divergence was largely driven by ancestral alternative isoforms, which, though present at low levels in related lineages that did not form radiations, increased in frequency during adaptive radiation. In addition, novel isoforms of craniofacial genes—some evolving within just a few thousand years—contributed further to adaptation. The rapid turnover of AS is consistent with periods of relaxed selection followed by directional selection on alternative isoforms and splice sites, a dynamic that may have preserved a rich cache of isoform variation in these radiations and enabled ecological diversification as adaptive zones became available. We argue that the interplay between splicing and different forms of selection facilitates the generation and maintenance of protein-coding diversity, promoting evolutionary innovation into many ecologically different species at extremely short timescales.